The Effect of Traumatic Experience to Personality Types in the Novel Girl in Pieces - Chrissy Oktaviani (Faculty of Letters Universitas Balikpapan, 2021)
This research focuses on the forms of traumatic experience that effect to personality types in the novel Girl in Pieces by Kathleen Glasgow. The aim of this research is to find the forms traumatic experience and the effect to personality types. The theory used in this research is Psychoanalysis by Carl Jung to find the effect of traumatic experience to personality types and theory by Gerald C. Davison to find the forms of traumatic experience. The method used in this study is a qualitative method that explained descriptively. The data in this research are primary data; novel Girl in Pieces and the secondary data; research, journal, thesis, internet and other related sources to the research. After going through the analysis, the researcher found that the forms of traumatic experience found based on the novel are flashbacks or re-experiencing traumatic events, arousal traumatic, and avoidance traumatic, whereas the flashback traumatic is the greatest effect on the introvert personality